Emissions from power generation in Greece: past data and possible future evolution - Samaras, Zissis; Tsilingiridis, George; Zachariadis, Theodoros (My University, 1995)
Current emissions from power plants in Greece are presented and analysed. The effect of Directives 88/609/EEC pertaining to the emissions of large combustion installations and 93/12/EEC on the sulphur content of gas oil is examined. It is concluded that Greek power plants can meet NOx emissions requirements without abatement measures, while new plants will have to employ SO2 reduction devices. The evolution of emissions from power generation up to the year 2010 is studied according to three technology-oriented scenarios, revealing that there is substantial emission reduction potential which, however, is not likely to be exhausted as Greece does not face severe acidification problems and NOx emissions are of concern in urban areas only, where power plants are not relevant.